ANALISIS KINERJA REKSA DANA SAHAM KONVENSIONAL DENGAN METODE JENSEN’S ALPHA, SORTINO DAN SNAIL TRAIL PERIODE 2017-2021 - Putu Riesty Masdiantini; Putu Tia Kertiani (Vokasi : Jurnal Riset Akuntansi, 2021)
Abstract This study aims to analyze the performance of conventional equity mutual funds using the Jensen's Alpha, Sortino, and Snail Trail for the period 2017 to 2021 and can provide information and consideration regarding equity mutual funds. The measurement method used in analyzing the performance of conventional equity mutual funds is Jensen's Alpha, Sortino, and Snail trails. The sample used is 32 conventional equity mutual funds with a period of 5 years 2017-2021. The benchmark for equity mutual funds used as a comparison is the JCI. The data collection technique used a purposive sampling method. Techniques Data analysis in this study using the Mann Whitney U-test. The results show that the performance of conventional equity mutual funds using Jensen's Alpha and Sortino have significant differences. Performance of conventional equity mutual funds using Jensen's Alpha and Sortino have significant differences and have inferior performance compared to market performance. Results from Snail The trail shows that the performance of conventional stock mutual funds is in quadrants 2 and 3. Equity funds located in quadrant 2 have a relatively high return and risk value and each stock mutual fund located in quadrant 3 has a relatively low return with high risk. The more often the location of the Snail Trail mutual funds is in quadrant 3, the more likely investors will switch to other types of mutual funds. Keywords: Performance, Equity Mutual Funds, Jensen's Alpha, Sortino, Snail Trail